Nuclear trafficking, histone cleavage and induction of apoptosis by the meningococcal App and MspA autotransporters - Khairalla, Ahmed S.; Omer, Sherko A.; Mahdavi, Jafar; Aslam, Akhmed; Dufailu, Osman A.; Self, Tim; Jonsson, Ann-Beth; Geörg, Miriam; Sjölinder, Hong; Royer, Pierre-Joseph; Martinez-Pomares, Luisa; Ghaemmaghami, Amir M.; et al. (Wiley, 2015)
Neisseria meningitidis, a major cause of bacterial meningitis and septicaemia, secretes multiple virulence factors, including the adhesion and penetration protein (App) and meningococcal serine protease A (MspA). Both are conserved, immunogenic, type Va autotransporters harbouring S6-family serine endopeptidase domains. Previous work suggested that both could mediate adherence to human cells, but their precise contribution to meningococcal pathogenesis was unclear. Here, we confirm that App and MspA are in vivo virulence factors since human CD46-expressing transgenic mice infected with meningococcal mutants lacking App, MspA or both had improved survival rates compared with mice infected with wild type. Confocal imaging showed that App and MspA were internalized by human cells and trafficked to the nucleus. Cross-linking and enzyme-linked immuno assay (ELISA) confirmed that mannose receptor (MR), transferrin receptor 1 (TfR1) and histones interact with MspA and App. Dendritic cell (DC) uptake could be blocked using mannan and transferrin, the specific physiological ligands for MR and TfR1, whereas in vitro clipping assays confirmed the ability of both proteins to proteolytically cleave the core histone H3. Finally, we show that App and MspA induce a dose-dependent increase in DC death via caspase-dependent apoptosis. Our data provide novel insights into the roles of App and MspA in meningococcal infection.